Fisheries sector under climate change in the coral triangle countries of Pacific Islands: Current status and policy issues - Valmonte-Santos, Rowena; Rosegrant, Mark W.; Dey, Madan M. (Elsevier, 2016)
Pacific Island countries face food insecurity, limited availability of productive agricultural land, and deteriorating coastal and marine biodiversity where communities rely on these resources for food and economic sustainability. Climate change further impends these Pacific Island countries, jeopardizing land and aquatic ecosystems in addition to threatening the livelihoods and socioeconomic conditions of coastal communities. The national governments of Pacific Island countries have created a number of development policies and plans to enhance the economic conditions, safety assurance, environmental conservation and preservation and other critical requirements of the national populace. This first paper in this Special Section aims to present the economic contributions, types of fisheries and common fishing practices/gears, and the institutional set-up and the national development plans and policies related to the fisheries sector in four Pacific countries namely, Fiji, Solomon Islands, Vanuatu, and Timor-Leste. The paper discusses the common issues and the collective action surrounding the fisheries sector in these Pacific countries. The final section of the paper provides conclusions based on the findings of the four subsequent papers of this Special Section.